Perancangan User Interface Website SMA Negeri 1 Salopa Menggunakan Metode Kansei Engineering - Adi Darmawan, Didit; Dwicahya Supriatman, RIan; Sidiq, Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
The development of website technology has provided a lot of convenience for developers to create products that suit the user's wishes. The purpose of this research is to produce an interface (UI) design design using the Kansei Engineering method and produce a website design that is in accordance with the needs and desires of users. This study uses the Kansei Engineering method with Kansei Engineering Type – I as a model in the research process. The statistical analysis used was Coefficient Correlation Analysis (CCA), Principal Component Analysis (PCA), and Factor Analysis (FA). Then the results of the analysis are translated into the arrangement of design elements using Partial Least Square (PLS).